Employing Extensive Reading Strategy to Improve Students’ Reading Comprehension (Pre-Experimental Research) - Patabang, Erika Nofianti Sera; Aeni, Nur; Munir, Munir (State University of Makassar, 2025)
Examining the efficacy of extended reading activities in enhancing eleventh graders' reading comprehension at SMA Katolik Cenderawasih Makassar was the primary goal of the study. The levels of pupils' literal, interpretive, and critical understanding were examined in this study. With the use of pre-and post-tests, the study was conducted using a pre-experimental approach. A total of 150 pupils from SMA Katolik Cenderawasih Makassar made up the study's population. Eighteen tenth graders served as the sample for this study. We used pre-and post-tests to get our data. Both the pre-and post-tests were narrative-text reading assessments. Results from the study demonstrated a statistically significant change between the pre-and post-treatment assessments. The average pre-test score for reading comprehension was 75.00. Students' reading comprehension scores improved by 11,42% as a result. The outcome of the data analysis will determine After the exam, the average score was 86.42, up from 75.00 before. The results show an improvement between the pre-and post-test scores, with the post-test mean score being higher than the pre-test mean score (86.42>75.00). The result was a 13.92% increase in performance between the pre-and post-tests. Based on the results of the hypothesis test, we may say that the Alternative Hypothesis (H1) is correct and that the Null Hypothesis (H0) is wrong. The study's author deduced this conclusion from the fact that pupils' reading comprehension levels were significantly different before and after the intervention. H1 was accepted as the alternative hypothesis while H0 was rejected as the null hypothesis. With a mean value of 0.4532, the N-Gain score falls into the